1992
DOI: 10.1088/0960-1317/2/1/004
|View full text |Cite
|
Sign up to set email alerts
|

A study of static friction between silicon and silicon compounds

Abstract: Presents results from measurements of static coefficient of friction between materials of interest to microelectromechanical systems (MEMS). The materials studied include silicon, silicon dioxide, and silicon nitride. Two measurement techniques have been used to this study. In the first technique, static friction between two millimeter-sized flat components was measured in a 10-6 Torr vacuum chamber. In the second technique, static friction between a three-millimeter radius aluminum bullet coated with a materi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0
1

Year Published

1996
1996
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(31 citation statements)
references
References 3 publications
3
26
0
1
Order By: Relevance
“…From these values, the frictional coefficient was calculated to 0.9 using the equation, µ = F/N, where µ is friction coefficient, F is friction force and N is normal force. According to the previous experimental reports, the static friction coefficient this experiment was comparable value [13][14][15][16]. This result suggested that the deformation of the silicon nanocontact caused the friction between tips.…”
Section: Discussionsupporting
confidence: 80%
“…From these values, the frictional coefficient was calculated to 0.9 using the equation, µ = F/N, where µ is friction coefficient, F is friction force and N is normal force. According to the previous experimental reports, the static friction coefficient this experiment was comparable value [13][14][15][16]. This result suggested that the deformation of the silicon nanocontact caused the friction between tips.…”
Section: Discussionsupporting
confidence: 80%
“…Many micromechanical components are based on monocrystalline, or less frequently on polycrystalline, silicon and often combined monolithically with microelectronic devices to produce sophisticated microsystems. Hence, tribological behaviour of silicon/silicon contacts during unlubricated sliding is of great importance for the performance ofmicromechanical systems [7][8][9]. Tribological studies on silicon have shown that under mild loading conditions the oxidation and/or the hydrooxidation of the Si surface determines friction and wear mechanisms during sliding contact [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…In order to prevent slipping of the clamps, the frictional force must be larger than the maximum output force of the motor. The coefficient of static friction between silicon nitride/silicon nitride contacts is between 0.55 and 0.85 [25]. Performance characteristics of the shuffle motors as predicted by the derived analytical models are summarized in Table 2.…”
Section: Output Forcementioning
confidence: 99%